Uranium resources associated with phosphoric acid production and water desalination in Saudi Arabia - Ud-Din Khan, Salah; Ahmad, Ashfaq; Khan, Rawaiz; Haneklaus, Nils (Frontiers in Earth Science, 2024)
Due to the rising demand for energy and the imperative to achieve net-zero carbon emissions, there is a growing focus on nuclear energy for its high efficiency as a clean energy source with minimal direct greenhouse gas emissions. The Kingdom of Saudi Arabia has set forth ambitious plans to construct multiple nuclear power plants in the near future. It is worth noting that phosphate rocks and desalination concentrate both contain relevant concentrations of naturally occurring uranium, presenting potential domestic uranium sources for the envisaged nuclear reactor fleet. This study offers a first systematic overview of the potential quantities of uranium that could theoretically be recovered during seawater desalination and phosphoric acid production in Saudi Arabia using best available technologies. It was found that in 2021 approximately 447-596 t natural uranium could have theoretically been recovered during phosphoric acid production in the Kingdom of Saudi Arabia. In addition, there were also 6.5 t uranium associated with seawater that was desalinated in 2021. If recovered the amounts would theoretically be able to provide 12-16% (uranium from phosphoric acid) and 0.2% (uranium from seawater desalination) of the annual uranium requirements of the projected Saudi nuclear power plant fleet in 2040. As a result, we strongly recommend fostering research on unconventional uranium recovery during phosphoric acid production by promoting public-private partnerships that have the potential to develop industrial scale solutions.